KMT2D p.Gln3575His segregating in a family with autosomal dominant choanal atresia strengthens the Kabuki/CHARGE connection. Issue 1 (7th November 2016) - Badalato, Lauren; Farhan, Sali M. K.; Dilliott, Allison A.; ,; Bulman, Dennis E.; Hegele, Robert A.; Goobie, Sharan L.
Abstract : Choanal atresia is rarely reported in Kabuki syndrome, but is a common feature of CHARGE syndrome. Otherwise, the two conditions have a number of overlapping features, and the molecular links between them have recently been elucidated. Here, we report a case of a mother and her two children who presented with congenital choanal atresia. We performed whole exome sequencing on DNA from the mother and her two unaffected parents, and identified a de novo, novel variant in KMT2D . KMT2D p.Gln3575His segregated with disease status in the family, and is associated with a unique and conserved phenotype in the affected family members, with features overlapping with Kabuki and CHARGE syndromes. Our findings further support the potential etiological link between these two classically distinct conditions. © 2016 Wiley Periodicals, Inc.